Sea-cliff Erosion with Rising Sea-Level along Shores Exposing Glacial Material in Atlantic Canada:: The Effect of Bedrock Slope and an Example from Isle Madame, Nova Scotia - Force, Eric (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2013)
SUMMARY Rapid retreat rates of sea cliffs exposing glacial material are a widespread problem, especially in Atlantic Canada, and one that will continue. Prediction of retreat rates at specific sites involves many variables, but a factor that has commonly been overlooked in such prediction is the slope of the bedrock surface under the glacial material. A glaciated bedrock platform is generally necessary to establish a stable situation of temporary equilibrium, and as sea-level rises, the bedrock slope determines the location of the new equilibrium position. An example from Nova Scotia shows that bedrock slope is so low on some coasts that the only long-range limiting factor is kinetic, i.e. how fast hydrodynamic energy can remove glacial material. Prediction of coastal retreat scenarios requires better information on the bedrock surface than is commonly available.